Lifestyle-Driven Preferences in Fruit Salad Consumption: Evidence from a Discrete Choice Experiment - Rayesa, Neza Fadia; Fitri, Kanissa Gita; Noor, Arif Yustian Maulana; Prasetyaningrum, Dian Islami; Ramadhan, Aditya Willy (HABITAT, 2026)
Purpose: This study aims to examine how lifestyle-based consumer segments influence preferences and willingness to pay (WTP) for fruit salad product attributes in urban Indonesia. Specifically, it investigates the moderating role of lifestyle dimensions—physical activity, dietary habits, mental wellness, and perceived health benefits in shaping consumer preferences for key product attributes. Design/Methodology/Approach: A quantitative study was conducted using a Discrete Choice Experiment (DCE) with a D-efficient design consisting of nine choice sets. Data were collected from 150 urban fruit salad consumers in Indonesia. Consumer preferences were analyzed using the Conditional Logit model, while marginal willingness to pay (MWTP) estimates were calculated using the Krinsky–Robb simulation approach. Lifestyle dimensions based on the Activities, Interests, and Opinions (AIO) framework were incorporated into the utility function to capture preference heterogeneity. Findings: The results indicate that consumers showed stronger preferences for fruit salad products with box packaging, online ordering platforms, and low-calorie nutritional labels. Lifestyle characteristics significantly influenced attribute preferences, with consumers exhibiting stronger dietary and mental wellness orientations demonstrating greater preferences for hygienic packaging and health-related labeling. The MWTP estimates further revealed that consumers were willing to pay price premiums for these preferred attributes, highlighting the economic value of health-oriented product differentiation in the urban fruit market. Originality/Value/Novelty: This study extends the application of Discrete Choice Experiments in agrifood marketing by integrating AIO-based lifestyle dimensions directly into the utility framework rather than treating lifestyle merely as a descriptive consumer characteristic. By providing monetized willingness-to-pay estimates for ready-to-eat fruit products in an emerging market, the study offers novel evidence on how lifestyle heterogeneity shapes consumer preferences and supports more effective product design, pricing,and marketing strategies for agrifood MSMEs and downstream horticultural businesses in urban Indonesia.